An Unusual Case of Placenta Percreta - Altay Gezer; Onur Güralp; Derya Kanza Gül; Orkun Çetin; Tarık Altınok (Gynecology Obstetrics & Reproductive Medicine, 2010)
Placenta percreta is a rare and serious complication of pregnancy. A 35 years old pregnant woman with severe preeclampsia at 36 gestational weeks delivered a live small for gestational age (SGA) fetus by cesarean section. During the operation, as the fetus had been delivered, the placenta was observed to be perforating the uterus at fundal region attaching to the omentum. This is a rare case of an intrauterine pregnancy with an extrauterine blood supply reaching almost term. Neither bleeding from placenta nor uterine rupture developed; and the infant was SGA and otherwise healthy.